KINERJA APARATUR DESA SEBAGAI UJUNG TOMBAK PELAYANAN PUBLIK DI DESA KERAMAT, KABUPATEN BANJAR - Sitna Hajar Malawat; Novita Octaviani (Jurnal Administrasi Publik dan Pembanguan, 2019)
The purpose of this study was to find out how the performance of the Village Apparatus was at the forefront of public services in the Keramat Village, Banjar Regency and what were the obstacles to the performance of the Keramat Village Apparatus, Banjar Regency. This research method uses a qualitative approach with a type of descriptive research. Data was collected by carrying out observations, documentation, and in-depth interviews with 6 (six) informants. This study uses interactive model data analysis techniques according to Miles & Huberman. The results of this study show that the performance of the sacred village apparatus as the spearhead of public services is seen in terms of understanding of duties, quality, the quantity of work and work commitments is quite good, but regarding timeliness, the Sacred Village Apparatus is still not disciplined. There are three factors that inhibit the performance of the Keramat Village Apparatus, Banjar Regency, namely the lack of village facilities and infrastructure, the limited ability of the village apparatus, and the low education of the village community in Keramat Village, Banjar Regency.